A Novel Viewpoint on the Anticipatory Postural Adjustments During Gait Initiation - Farinelli, Veronica; Bolzoni, Francesco; Marchese, Silvia Maria; Esposti, Roberto; Cavallari, Paolo (Frontiers in Human Neuroscience, 2021)
Anticipatory Postural Adjustments (APAs) are coordinated muscular activities that precede voluntary movements with the aim of counteracting the associated postural perturbations. Many studies about gait initiation call APAs those activities that precede heel-off of the leading foot, thus taking heel-off as the onset of voluntary movement. In particular, leg muscles drive the Center of Pressure (CoP) both laterally, to shift the body weight over the trailing foot and backward, to create a disequilibrium torque pushing forward the Centre of Mass (CoM). However, since subjects want to propel their body rather than lift their foot, the onset of gait should be the CoM displacement, which starts with the backward CoP shift. If so, the leg muscles driving such shift are the prime movers. Moreover, since the disequilibrium torque is mechanically equivalent to a forward force acting at the pelvis level, APAs should be required to link the body segments to the pelvis: distributing such concentrated force throughout the body would make all segments move homogeneously. In the aim of testing this hypothesis, we analyzed gait initiation in 15 right-footed healthy subjects, searching for activities in trunk muscles that precede the onset of the backward CoP shift. Subjects stood on a force plate for about 10 seconds and then started walking at their natural speed. A minimum of 10 trials were collected. A force plate measured the CoP position while wireless probes recorded electromyographic activities. Recordings ascertained that at gait onset APAs develop in trunk muscles. On the right side, Rectus and Obliquous Abdominis were activated in 11 and 13 subjects, respectively, starting in average 33 and 54 ms before CoP shift; Erector Spinae at L2 and T3 levels were instead inhibited (9 and 7 subjects, 104 and 120 ms). On the contralateral side, the same muscles showed excitatory APAs (abdominals in 11 and 12 subjects, 27 and 82 ms; Erector Spinae in 10 and 7 subjects, 75 and 32 ms). Present results provide a novel framework for distinguish postural from voluntary actions, which may be relevant for gait disorders diagnosis and rehabilitation.